From Headlines to Awareness: Examining the Minimal Impact of Media on Climate Action in the United States - James, Patrick (Asian Journal of Media and Communication, 2025)
This study examines the influence of media consumption on climate change perceptions and pro-environmental behaviors in the United States, incorporating demographic variations and trust in media as potential mediating and moderating factors. Using a cross-sectional survey of 548 U.S. adults aged 18 to 35, the study employs the Elaboration Likelihood Model (ELM) to assess how different media sources and processing routes shape climate-related engagement. The findings highlighted that despite extensive climate media coverage, behavioral shifts remain limited, highlighting a critical gap in climate communication effectiveness, such as voting based on climate policies or financial contributions to environmental organizations. The findings also reveal that media exposure alone does not drive climate action, demographics and media tr ust fail to enhance engagement, suggesting other factors like ideology or personal experience play a stronger role. These findings challenge prior research that emphasizes media trust and demographic characteristics as key determinants of climate action. The study highlights the limitations of media exposure in translating awareness into meaningful behavioral change and underscores the need for targeted climate communication strategies.